Hubungan Tingkat Pengetahuan dan Sikap Ibu terhadap Tindakan Mencuci Tangan dalam Perawatan Tali Pusat Bayi Baru Lahir - yeni letari (Jurnal Medika Hutama, 2021)
Umbilical cord infection is an infection that occurs in the umbilical cord and the surrounding tissue is characterized by redness, swelling in the umbilical cord. One effort to prevent the occurrence of umbilical cord infection is to take action to hands washing in the care of the umbilical cord. Hand washing aims to eliminate or reduce germs and bacteria that stick to the hands so that the germs and bacteria do not enter the umbilical cord injury. This research aims to determine the correlation between the level of knowledge and attitudes of mother to the act of hands washing in the care of newborn baby cord in the working area of Payung Sekaki Health Center. This type of research is quantitative research with cross-sectional design using purposive sampling technique. The univariate result of 42 respondents found that the majority of mother had a good level of knowledge as much 27 respondents (64,3%), the majority of mothers attitudes were good as many 23 respondents (54,8%) and the majority of mothers did the act of hands washing their in umbilical cord care as many as 37 respondents (88,1%). The result of bivariate using square test with alternative fisher exact test fro knowledge and Kolmogorov-smirnov test for attitude, showed that there was a correlation between the level of maternal knowledge of the act of hands washing in infant umbilical cord care with a p value 0,004 less than 0,05 and there was a no correlation between maternal attitudes toward the act of hands washing in umbilical cord care with p value 0,998 is smaller than 0,05. Based on the result of the analysis it is expected that health workers can maintain and increase the mothers knowledge by providing health education that always hands washing in any action especially actions related to newborns.